Long-Term Prognostic Factors in Patients With Antineutrophil Cytoplasmic Antibody-Associated Vasculitis: A 15-Year Multicenter Retrospective Study - Liao, Qian-Qian; Ren, Ya-Fei; Zhu, Ke-Wei; Qin, Dong; Mo, Yan-Ju; Cong, Shan; Wu, Juan; Wang, Chun-Ying; Cui, Xiao-Jiao; Xu, Hong-Zhen; Guo, Lin-Zheng; Zhang, You-Yan; et al. (Frontiers in Immunology, 2022)
Background: Antineutrophil cytoplasmic antibody (ANCA)-associated vasculitis (AAV) is a multisystem autoimmune disease with small vessel involvement. In AAV, microscopic polyangiitis (MPA) and granulomatosis with polyangiitis (GPA) are major clinicopathologic variants, and myeloperoxidase (MPO) and proteinase 3 (PR3) are major target antigens. The objective of the study was to explore the predictive factors for long-term survival in AAV patients. Materials and methods: A multicenter retrospective study was carried out in 407 patients between 2005 and 2020. Clinical parameters were obtained from laboratory tests including the ANCA types, antinuclear antibody (ANA), extractable nuclear antigen (ENA), anti-streptolysin O (ASO), glomerular filtration rate (GFR), and the examinations for the blood routine, liver function, renal function, and immunity, etc. The data for clinical parameters were collected from electronic medical records (EMRs), and the data for patient survival were acquired through regular follow-up. The association of clinical parameters and overall survival (OS) along with 3-year and 5-year survival rates were analyzed, and the nomogram as a predictive model was established according to the analysis results. Results: In the present study, 336 (82.6%) patients and 46 (11.3%) patients were diagnosed with MPA and GPA, respectively. The mean and median OS for all the patients were 2285 days and 2290 days, respectively. The 1-year, 3-year, 5-year, and 10-year cumulative survival rates for all the patients were 84.2%, 76.3%, 57.2%, and 32.4%, respectively. Univariate and multivariate survival analyses indicated that the independent prognostic factors included age, pathological categories (MPA, GPA, and the others), serum ANCA types (negative, positive for MPO and/or PR3), ANA, ASO, GFR, lymphocyte, neutrophil-to-lymphocyte ratio (NLR), and CRP (C-reactive protein), and these clinical parameters except ASO were used to construct a nomogram. The predictive model for 3-year and 5-year survival rates had a C-index of 0.721 (95% CI 0.676 – 0.766). The calibration curve showed that the predicted values of the nomogram for 3-year and 5-year survival rates were consistent with practical observed values, and decision curve analysis (DCA) further demonstrated the practicability and accuracy of the predictive model. Conclusion: Laboratory tests at diagnosis had great significance in the prediction of long-term survival in AAV patients.